Description Analysis of Muslim Millennial Trust and Comfort in Using Crowdfunding Platforms for Donation - Azhar Alam; Luthfi Aria Widyatama Mirza; Chabibatul Mu’awanah (Future Science, 2020)
This study aims to determine the description of Muslim millennials' trust and comfort when donating on crowdfunding platforms. This study took data research from millennials Muslim users of crowdfunding donation platform kitabisa.com who have donated two times or more. This study interviewed ten respondents of crowdfunding platforms to determine why they use crowdfunding platforms as media in terms of trust and convenience. This research uses qualitative and descriptive phenomenological research to know a particular phenomenon by understanding the meaning of an individual's experience related to a specific phenomenon. This study's finding shows that the description of things that affect their trust level in donating on crowdfunding platforms is transparency, legalization, and secure personal data protection. In contrast, the description of things that affect comfort level is time efficiency, simplicity of features, and flexibility in accessing. This research is expected to support donation, and zakat institutions use crowdfunding platforms to help their function in Muslims' welfare beset by difficulties.